SOME ASPECTS OF THE DEVELOPMENT OF LEGISLATION ON THE PROTECTION AND USE OF WILDLIFE - Zhandauova Жанара Абдылдаевна; Kayzhakparova Аида Бахытжановна; Zhaxylykova Алуа Курмангалиевна (Scientific and legal journal «Bulletin of the Institute of Legislation and Legal Information of the Republic of Kazakhstan», 2025)
Today, the legislation of the Republic of Kazakhstan in the field of protection, reproduction and use of wildlife is a sub-branch of environmental legislation, consisting of the Environmental Code of the Republic of Kazakhstan, the Laws of the Republic of Kazakhstan «On protection, reproduction and use of wildlife», «On responsible treatment of animals», «On specially protected areas», etc. The article is based on the results of an analysis of the effectiveness of legislation in the field of protection and use of wildlife. The article suggests some ways to improve the legislation of the Republic of Kazakhstan in the field of protection and use of wildlife, developed scientifically sound recommendations and proposals for their implementation. In this regard, the authors identified gaps, as well as duplicate norms, conducted an audit of the conceptual framework and an assessment of the effectiveness of the implementation of the norms of the Law of the Republic of Kazakhstan «On Responsible Treatment of Animals». A review and analysis of scientific and legal approaches to the protection and use of wildlife has been conducted, on the basis of which it is proposed to update the terminology used within the framework of legislation: «service animals», «farm animals». Thus, the relevance of this study is enhanced due to the objective needs to further improve the effectiveness of legislation in the field of protection and use of wildlife, its consistency and consistency.